Compound heterozygous KCTD7 variants in progressive myoclonus epilepsy. (3rd April 2021) - Burke, Elizabeth A.; Sturgeon, Morgan; Zastrow, Diane B.; Fernandez, Liliana; Prybol, Cameron; Marwaha, Shruti; Frothingham, Edward P.; Ward, Patricia A.; Eng, Christine M.; Fresard, Laure; Montgomery, Stephen B.; Enns, Gregory M.; et al.
Abstract: KCTD7 is a member of the potassium channel tetramerization domain-containing protein family and has been associated with progressive myoclonic epilepsy (PME), characterized by myoclonus, epilepsy, and neurological deterioration. Here we report four affected individuals from two unrelated families in which we identified KCTD7 compound heterozygous single nucleotide variants through exome sequencing. RNAseq was used to detect a non-annotated splicing junction created by a synonymous variant in the second family. Whole-cell patch-clamp analysis of neuroblastoma cells overexpressing the patients' variant alleles demonstrated aberrant potassium regulation. While all four patients experienced many of the common clinical features of PME, they also showed variable phenotypes not previously reported, including dysautonomia, brain pathology findings including a significantly reduced thalamus, and the lack of myoclonic seizures. To gain further insight into the pathogenesis of the disorder, zinc finger nucleases were used to generate kctd7 knockout zebrafish. Kctd7 homozygous mutants showed global dysregulation of gene expression and increased transcription of c-fos, which has previously been correlated with seizure activity in animal models. Together these findings expand the known phenotypic spectrum of KCTD7 -associated PME, report a new animal model for future studies, and contribute valuable insights into the disease.